ENHANCING EFL LEARNERS' SPEAKING ABILITIES THROUGH THE USE OF PODCASTS AND ONLINE DRAMA SCRIPTS - Suseno, Edy (Sanata Dharma University Yogyakarta, 2025)
It is crucial to communicate using a language. However, a lot of EFL students had trouble expressing their ideas. 25 freshmen joined the therapy to make it better. To improve the effectiveness of the teaching-learning process, the teacher created a WhatsApp group application during pre-learning. The instructor guided the pupils in creating sentences by teaching them the lexico-grammar of bilingualism. The teacher displayed the podcast's URL on the screen to help students coordinate their contextual usage. Using this kind of content, the students improved their noticing, listening, repeating, shadowing, and translating skills. It is the audio and video version of the podcast. The pupils must improve their capacity for information exchange. In order to appease them, the instructor displayed the URL of an online drama script on the screen. The pupils rehearsed the role play in order to finish the assignment. The study's results were then qualitatively examined. As a result of using podcasts and online theatrical scripts to study speaking, the students' capacity for presenting ideas increased. The novelty is this approach leverages the power of multimedia to create an engaging and authentic learning experience that goes beyond traditional classroom activities. Teachers must use these kinds of findings when instructing related subjects. It also encourages other researchers to carry out studies in related disciplines.